2005
DOI: 10.3171/jns.2005.102.2.0246
|View full text |Cite
|
Sign up to set email alerts
|

A series of 397 peripheral neural sheath tumors: 30-year experience at Louisiana State University Health Sciences Center

Abstract: The majority of tumors were benign PNSTs from the brachial plexus region. Most of the benign PNSTs in all locations were neurofibromas, with sporadic neurofibromas predominating. Similar numbers of schwannomas were found in the upper and lower extremities, whereas neurofibromas were more prevalent in the upper extremities. Despite aggressive limb-ablation or limb-sparing surgery plus adjunctive therapy, malignant PNSTs continue to be associated with high morbidity and mortality rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
229
3
18

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 283 publications
(274 citation statements)
references
References 40 publications
9
229
3
18
Order By: Relevance
“…The majority of the tumors were reported as benign peripheral nerve sheath tumors from the brachial plexus region. Neurofibromas were more prevalent in the upper extremities [5]. In a series of 40 neural sheath tumors Lusk et al [6] found 26 neurofibromas, nine of which were associated with von Recklinghausen's disease (VRD).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the tumors were reported as benign peripheral nerve sheath tumors from the brachial plexus region. Neurofibromas were more prevalent in the upper extremities [5]. In a series of 40 neural sheath tumors Lusk et al [6] found 26 neurofibromas, nine of which were associated with von Recklinghausen's disease (VRD).…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative electrophysiological neuromonitoring is used to demonstrate the proper management of a brachial plexus nerve sheath tumor excision [10]. Despite aggressive limb ablation or limb sparing surgery plus adjunctive therapy, malignant peripheral nerve sheath tumors continues to be associated with high morbidity and mortality rates [5].…”
Section: Discussionmentioning
confidence: 99%
“…Multifocal MPNST without neurofibromatosis is a rare occurrence, although a few instances have been reported in literature. Despite aggressive limb ablation or limb sparing surgery and adjunctive therapy MPNSTs continue to be associated with high morbidity and mortality [3].…”
Section: Introductionmentioning
confidence: 99%
“…1,5 Intraoperative electrical stimulation of motor nerve fascicles and direct recording allow the surgeon to identify involved and nearby functional nerves and avoid damaging them during tumor resection. 3 With a negative electrical map over the surface of the mass, the tumor capsule can be safely entered and the tumor resected without violating or damaging functional nerve fibers.…”
mentioning
confidence: 99%
“…3,10 Intraneural tumors may involve 1 or multiple nerve fascicles and may originate from deep within the nerve subsequently splaying apart fascicles as the tumor expands, or they may be attached to a superficial fascicle and thereby displacing the remainder of the nerve to one direction.…”
mentioning
confidence: 99%